ECG method for positioning the tip of peripherally inserted central catheters in patients with atrial fibrillation. Issue 3 (17th February 2022) - Zhao, Conghui; Zhu, Yuxin; Yin, Xinxin; Zhang, Congcong; He, Yingxia; Gao, Jingfang
Abstract: Objective: To observe the changes of F waves on electrocardiograms (ECGs) in patients with persistent atrial fibrillation during the insertion of a peripherally inserted central catheter (PICC), and to analyze the application effect of the ECG method (through F wave changes) for guiding PICC tip positioning. Methods: Seventy‐two patients who met the inclusion criteria and needed a PICC catheter were selected as the research subjects. We observed waveforms in the ECGs when the tip of the catheter reached a predetermined position. The chest X‐ray results were used as the gold standard to calculate the sensitivity and specificity, and judge the safety and accuracy of ECG‐guided PICC tip positioning in patients with atrial fibrillation. Results: Of the 72 patients, there was no significant difference between the ECG method and chest X‐ray results (χ 2 = 0.2, p > 0.05). Sixty‐one patients had F wave changes on ECG and 10 had no obvious changes (X‐ray results confirmed that five patients had a tip position that was too shallow, two had ectopic tip positions, and three were located in the correct place). The sensitivity of the method was 95.7% and the specificity was 80%. Conclusion: As the ECG baselines of patients with persistent atrial fibrillation were difficult to judge and the F wave was irregular, we found that the F wave was significantly higher than before catheter insertion and fell back while withdrawing the catheter, so the catheter should be fed until the F wave significantly increased as the correct position of the catheter tip.